EFFICIENT MOLYBDENUM CATALYZED CHEMOSELECTIVE, SOLVENT-FREE OXIDATION OF SULFIDES TO SULFONES AT ROOM TEMPERATURE - Hadigavabar, Ali Dadashi; Tabatabaeian, Khalil; Zanjanchi, Mohammad Ali; Mamaghani, Manouchehr (Journal of the Chilean Chemical Society, 2018)
An efficient and reusable molybdenum-based catalyst has been prepared by tethering dioxomolybdenumacetylacetonate complex, MoO2(acac)2, via post-synthesis modification of zeolite beta. The catalyst has been characterized by Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy-energy dispersive X-ray analysis (SEM-EDX) and inductively coupled plasma (ICP). The catalyst exhibited very high activity for the selective oxidation of sulfides to sulfones at room temperature. The catalyst can be recycled and reused four times without significant loss of activity.